Study of the effect of redox mediators on the decolorization of azo dyes by ascomycete yeasts - Ramalho, Patrícia Alexandra Costa Ferreira (2003)
Apresentação efectuada no "ECCOXXII – Braga 2003 : Biological Resources Centres and the Use of Microbes", em Braga, Portugal, em Setembro de 2003.